Leptin decreases circulating inflammatory IL‐6 and MCP‐1 in mice. (29th November 2018) - Hoffmann, Annett; Ebert, Thomas; Klöting, Nora; Kolb, Marlen; Gericke, Martin; Jeromin, Franziska; Jessnitzer, Beate; Lössner, Ulrike; Burkhardt, Ralph; Stumvoll, Michael; Fasshauer, Mathias; Kralisch, Susan
Abstract: Leptin influences inflammation and immune response. Dose‐dependent effects of leptin on biomarkers of inflammation have not been studied in vivo, so far. Leptin‐deficient low‐density lipoprotein receptor (LDLR) knockout (LDLR −/− ; ob/ob ) female mice were treated with three different leptin doses or saline for 12 weeks. The effect of leptin on plasma interleukin (IL)‐6 and monocyte chemoattractant protein (MCP)‐1 concentrations and Il‐6 and Mcp‐1 mRNA expression in vivo were assessed. Macrophage infiltration in epididymal adipose tissue (epiAT) after leptin treatment was determined by quantitative immunohistochemical analysis. Aortic root atherosclerotic lesions were analyzed by oil red O staining. Mean plasma IL‐6 and MCP‐1 decreased significantly in the 3.0 mg/kg BW/day group as compared to control mice (both P < 0.01). Messenger RNA expression of Il‐6 and Mcp‐1 was significantly down‐regulated by leptin treatment in different adipose tissues in vivo . Characteristic crown‐like structures formed by adipose tissue macrophages were significantly reduced by leptin treatment in epiAT. Recombinant leptin dose‐dependently diminished plaque area in the aortic root. Leptin administration within the subphysiological to physiological range diminishes circulating pro‐inflammatory IL‐6 and MCP‐1. Reduction of Il‐6 and Mcp‐1 gene expression in adipose tissue, as well as decreased adipose tissue macrophage infiltration might contribute. © 2018 BioFactors, 45(1):43–48, 2019